2023
DOI: 10.1002/smll.202208062
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Crystal Nanowire Cesium Tin Triiodide Perovskite Solar Cell

Abstract: This work reports for the first time a highly efficient single‐crystal cesium tin triiodide (CsSnI3) perovskite nanowire solar cell. With a perfect lattice structure, low carrier trap density (≈5 × 1010 cm−3), long carrier lifetime (46.7 ns), and excellent carrier mobility (>600 cm2 V−1 s−1), single‐crystal CsSnI3 perovskite nanowires enable a very attractive feature for flexible perovskite photovoltaics to power active micro‐scale electronic devices. Using CsSnI3 single‐crystal nanowire in conjunction with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 75 publications
0
4
1
Order By: Relevance
“…The experimental values on CsSnI 3 were m h = 0.25-628 cm 2 V À1 s À1 and m e = 1.05-2320 cm 2 V À1 s À1 . [28][29][30][31][32][33][34][35] Some reported mobilities in experiments were much lower than our theoretical predictions. This investigation predicted the intrinsic mobility, which was the upper limit that the perovskite might achieve.…”
Section: Screening Mobility Through Empirical Modelscontrasting
confidence: 70%
See 1 more Smart Citation
“…The experimental values on CsSnI 3 were m h = 0.25-628 cm 2 V À1 s À1 and m e = 1.05-2320 cm 2 V À1 s À1 . [28][29][30][31][32][33][34][35] Some reported mobilities in experiments were much lower than our theoretical predictions. This investigation predicted the intrinsic mobility, which was the upper limit that the perovskite might achieve.…”
Section: Screening Mobility Through Empirical Modelscontrasting
confidence: 70%
“…Unfortunately, because of unavoidable impurities and technical differences during the experimental process, the measurement results were inconsistent. The experimental mobilities of CsPbI 3 and CsSnI 3 were 1.72-270 cm 2 V À1 s À1 23-27 and 0.25-2320 cm 2 V À1 s À1 , [28][29][30][31][32][33][34][35] respectively. Intrinsic defects caused extra scattering, which reduced mobility.…”
Section: Introductionmentioning
confidence: 90%
“…Tremendous efforts have been devoted to the development of high‐performance n–i–p structured (conventional) inorganic perovskite solar cells (PSCs), including optimization of perovskite structure, [ 9,10 ] composition, [ 11–15 ] crystallinity, [ 16–19 ] and interface. [ 20–24 ] As a result, the PCE has been boosted from 2.5% in 2015 [ 25 ] to 21.7% recently.…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, Dai et al reported an all-inorganic single-crystal CsSnI 3 perovskite NWs with a perfect lattice structure, and the HRTEM demonstrated that the singlecrystal CsSnI 3 NWs were grown along the (002) direction (figure 7(a)). Additionally, the CsSnI 3 NWs exhibited low carrier trap density (≈5 × 10 10 cm −3 ), long carrier lifetime (46.7 ns), and excellent carrier mobility (<600 cm 2 V −1 s −1 ) [102]. Taking advantage of the low defect density of perovskite single-crystal NWs, some interesting work was reported.…”
Section: D Perovskite Nanostructuresmentioning
confidence: 99%